A microfluidic immunomagnetic bead-based system for the rapid detection of influenza infections: from purified virus particles to clinical specimens - Hung, Lien-Yu (Biomed Microdevices, 2013)
Seasonal and novel influenza infections have the potential to cause worldwide pandemics. In order to properly treat infected patients and to limit its spread, a rapid, accurate and automatic influenza diagnostic tool needs to be developed. This study therefore presents a new integrated microfluidic system for the rapid detection of influenza infections. It integrated a suction-type, pneumatic-driven microfluidic control module, a magnetic bead-based fluorescent immunoassay (FIA) and an end-point optical detection module. This new system can successfully distinguish between influenza A and B using a single chip test within 15 min automatically, which is faster than existing devices. By utilizing the micromixers to thoroughly wash out the sputum-like mucus, this microfluidic system could be used for the diagnosis of clinical specimens and reduced the required sample volume to 40 μL. Furthermore, the results of diagnostic assays from 86 patient specimens have demonstrated that this system has 84.8 % sensitivity and 75.0 % specificity. This developed system may provide a powerful platform for the fast screening of influenza infections. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s10544-013-9753-0) contains supplementary material, which is available to authorized users.